2019
DOI: 10.1145/3344210
|View full text |Cite
|
Sign up to set email alerts
|

Density-Friendly Graph Decomposition

Abstract: Decomposing a graph into a hierarchical structure via k-core analysis is a standard operation in any modern graph-mining toolkit. k-core decomposition is a simple and efficient method that allows to analyze a graph beyond its mere degree distribution. More specifically, it is used to identify areas in the graph of increasing centrality and connectedness, and it allows to reveal the structural organization of the graph.Despite the fact that k-core analysis relies on vertex degrees, k-cores do not satisfy a cert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…A possible answer is that the k-core can behave counter-intuitively, with respect to the intuitive concept of the edge density, introduced in Section 3.1.1. Specifically, Tatti and Gionis [10] demonstrated that the k-core can have lower edge density than an -core with < k in the same graph, even though we intuitively expect that a core with higher k value should be more dense.…”
Section: K-core: Subgraph With Largest Minimum Degreementioning
confidence: 85%
“…A possible answer is that the k-core can behave counter-intuitively, with respect to the intuitive concept of the edge density, introduced in Section 3.1.1. Specifically, Tatti and Gionis [10] demonstrated that the k-core can have lower edge density than an -core with < k in the same graph, even though we intuitively expect that a core with higher k value should be more dense.…”
Section: K-core: Subgraph With Largest Minimum Degreementioning
confidence: 85%
“…Tatti and Gionis [59] define density-friendly graph decomposition, where the density of the inner subgraphs is higher than the density of the outer subgraphs. Govindan et al [31] propose k-peak decomposition which allows finding local dense regions in contrast with classic core decomposition.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The multiscale graph G i+1 is constructed from the previous finer scale graph G i by collapsing together the nodes and edges that have similar matching criteria. The matching can be computed in different ways, for example, by using aggregates [2]; by considering dominant route flows [34]; or based on node density [35]. In this work, the matching is based on the edge difference or variance of the edge weights.…”
Section: Heuristic Coarsening Framework For Multiscale Graph Genmentioning
confidence: 99%